2011
DOI: 10.1523/jneurosci.6663-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual Response of Serotonergic Neurons after CNS Injury: Lack of Axonal Dieback and Enhanced Sprouting within the Inhibitory Environment of the Glial Scar

Abstract: Serotonergic neurons possess an enhanced ability to regenerate or sprout after many types of injury. To understand the mechanisms that underlie their unusual properties, we used a combinatorial approach comparing the behavior of serotonergic and cortical axon tips over time in the same injury environment in vivo and to growth-promoting or -inhibitory substrates in vitro. After a thermocoagulatory lesion in the rat frontoparietal cortex, callosal axons become dystrophic and die back. Serotonergic axons, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 69 publications
3
70
0
Order By: Relevance
“…23 Pilot studies of sumatriptan use in PTM have demonstrated efficacy in the mTBI population in the acute setting. 25,26 The FSHC and CC both express the 5-HT 1a receptor, 23,[27][28][29] for which serotonin is a partial agonist. Although quantitative use of DTI metrics in the clinical setting is currently limited by the lack of universally accepted normative data, demonstrating injured regions associated with PTM is the first step toward an individual diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…23 Pilot studies of sumatriptan use in PTM have demonstrated efficacy in the mTBI population in the acute setting. 25,26 The FSHC and CC both express the 5-HT 1a receptor, 23,[27][28][29] for which serotonin is a partial agonist. Although quantitative use of DTI metrics in the clinical setting is currently limited by the lack of universally accepted normative data, demonstrating injured regions associated with PTM is the first step toward an individual diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that axons that normally display a high rate of synaptic and branch remodelling, that is, from Layer (L) 6 cortical cells would more readily respond to a lesion than axons that are typically more stable, that is, thalamocortical axons (TCA) projecting to the upper layers of the cortex 8 . This intrinsically specified plasticity is reminiscent of the differences in regeneration between different axonal tracts following injury [9][10][11] .…”
mentioning
confidence: 99%
“…The ability of adult neurons of the CNS to regenerate their axons in response to injury is limited in many neuronal types depending on both intrinsic and extrinsic factors (3)(4)(5)(6)(7)(8). Axons in the CNS represent a challenging site for targeted manipulation and in vivo imaging, and little is known about their postlesional reactive plasticity and how this is regulated by molecular mediators.…”
mentioning
confidence: 99%